2011
DOI: 10.1111/j.1600-079x.2011.00968.x
|View full text |Cite
|
Sign up to set email alerts
|

Description of the constitutive activity of cloned human melatonin receptors hMT1 and hMT2 and discovery of inverse agonists

Abstract: Melatonin receptors have been described to activate different G protein-dependent signaling pathways, both in laboratory, heterologous, cellular models and in physiological conditions. Furthermore, the constitutive activity of G protein-coupled receptors has been shown to be key in physiological and pathological conditions. In the case of melatonin receptors, information is rather scare and concerns only MT1 receptors. In the present report, we show that the G protein-coupled melatonin receptors do have a cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 54 publications
3
16
0
Order By: Relevance
“…This is further confirmed by the observation of a slight but significant constitutive activation of Gαi in the presence of the ligand-free receptor. Indeed, this is consistent with the constitutive activity that has been reported for the human MT1 receptor studied in a cellular environment [31].…”
Section: Resultssupporting
confidence: 91%
“…This is further confirmed by the observation of a slight but significant constitutive activation of Gαi in the presence of the ligand-free receptor. Indeed, this is consistent with the constitutive activity that has been reported for the human MT1 receptor studied in a cellular environment [31].…”
Section: Resultssupporting
confidence: 91%
“…This small amount of melatonin would be sufficient to physiologically activate high affinity MT 1 melatonin receptors to modulate behavioral functions (Dubocovich et al, 2010). It is also possible that MT 1 melatonin receptors expressed in a constitutively active form (Browning et al, 2000; Devavry et al, 2012; Soares et al, 2003) may signal in the absence of melatonin to regulate pathways modulating behaviors. In summary genetic deletion of MT 1 melatonin receptors may impair activation of melatonin receptor signaling by circulating melatonin and/or by the absence of functional constitutively active receptors.…”
Section: E Discussionmentioning
confidence: 99%
“…Our approach allowed us to demonstrate that melatonin receptors display two binding sites, as shown by [ 3 H]‐melatonin saturation studies conducted under a variety of experimental conditions encompassing inter‐species differences in receptor sequence as well as differences in host cell, binding to cell membranes and binding to live cells. We recently reported that when expressed in recombinant systems, melatonin receptors undergo constitutive coupling to G‐proteins (Devavry et al ., 2012b). We therefore hypothesized that the two sites we report here were comparable to two states of receptor activation.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we report a comparative description of the molecular pharmacologies of hMT 1 and hMT 2 using these two radioligands. Our study confirms our recent findings that hMT 1 and hMT 2 are spontaneously expressed, as being pre‐coupled to G‐proteins (Devavry et al ., 2012b), and that it is in this state that the receptors exhibit different pharmacologies; they have the same ligand‐binding properties when they are un‐coupled from G‐proteins.…”
Section: Introductionmentioning
confidence: 99%